ТЕХНОЛОГИЯ ОБОГАТЕНИЯ СОСТАВА КАМБИКОРМА ЗЕРНОВЫМИ СМЕСЯМИ - Ирназаров Шухрат Исматуллаевич (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Аннотация: The most important factors affecting the quality of the grown grain are the state of the environment, the characteristics of agricultural technology, temperature and humidity, the occurrence of various diseases and defects that can worsen its technological and consumer advantages. Man has a strong influence on grain grown in the fields: the introduction of mineral and organic fertilizers, pesticides, the appearance of acid rain, emissions from industrial enterprises and vehicles, which ultimately can cause environmental problems in the production of feed. The compound feed contains up to 70% of cereals, leguminous crops, by-products of grain processing, so environmentally friendly grain is a guarantee of high-quality feed